Seismic Performance of Base-Isolated and Conventional Hospital Buildings in the February 6, 2023, Earthquakes - Yenidogan, Cem (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
February 6, 2023, earthquakes are one of the most destructive cascading earthquakes of the last century. Following the February 6, 2023, earthquakes, the official death toll exceeded 60000 in Turkiye and Syria, and hundreds of thousands of injuries were reported from healthcare facilities in the earthquakeaffected region in Turkiye. Since hospital buildings are critical facilities, their seismic performance is expected to outperform the seismic performance of residential buildings during major earthquakes. Moreover, base-isolated facilities should meet the continued functionality as declared by the circular of the Ministry of Health enforced in 2013 and 2018 for hospital buildings with a bed capacity of over 100 in high-seismicity regions. In the earthquake-affected region, eleven seismically isolated hospital buildings and hundreds of conventionally constructed healthcare facilities were subjected to two main shocks and aftershock sequences during the February 6, 2023, earthquakes. In this study, the seismic performance of fixed-based and seismically isolated hospital buildings was examined under varying levels of earthquake ground motions during the February 6, 2023, earthquake sequence based on the preliminary findings of field trip observation.
Keywords: Seismic Isolation; Field Survey; Hospital Damage; Sliding Isolation; Construction & Building Technology; Engineering